Implementasi Pengelolaan Kelas pada Mata Pelajaran PAI - Pajria, Siti Zahra; Karyawati, Lilis; Karnia, Nia (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This research aims to deeply explore and reveal how the implementation of classroom management is applied in the teaching and learning activities of Islamic Religious Education (PAI) subjects at SMP Negeri 2 Karawang Timur. A qualitative method with a case study design is employed, utilizing classroom observations, interviews with both teachers and students, as well as analyzing various relevant documents to collect research data. The results indicate that PAI teachers at SMP Negeri 2 Karawang Timur have successfully implemented classroom management effectively, as evidenced by their ability to organize classes during PAI teaching and learning activities effectively. The classrooms are well-organized, and the instructional aids provided by the school are used effectively. Efforts to address challenges and difficulties in classroom management, particularly in teaching PAI in Grade VIII, involve reaching an agreement on classroom learning contracts developed and approved jointly by teachers and students.